1995
DOI: 10.1002/jlb.57.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of L-selectin and CD18 on bovine neutrophils by glucocorticoids: effects of cortisol and dexamethasone

Abstract: The responsiveness of bovine neutrophil L-selectin and CD18 to in vivo glucocorticoid administration was characterized by flow cytometric analysis. Blood was sampled intensively from dairy cows treated for 3 days with placebo, cortisol, or dexamethasone. Immunostaining was performed on whole blood (100 microliters) that was left unstimulated or was stimulated with platelet-activating factor (PAF; 1 microgram/ml blood) prior to incubation with fluorescein isothiocyanate-conjugated monoclonal antibodies against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
3
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(156 citation statements)
references
References 26 publications
12
138
3
3
Order By: Relevance
“…Treatment with dexamethasone and cortisol resulted in down-regulation of membrane bound L-selectin [4] on resting and activated PMN. Burton and Kehrli [3] also observed that glucocorticoidmediated down regulation of membrane bound L-selectin and CD18 on PMN increased mammary gland susceptibility to Staphylococcus aureus following experimental challenge.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment with dexamethasone and cortisol resulted in down-regulation of membrane bound L-selectin [4] on resting and activated PMN. Burton and Kehrli [3] also observed that glucocorticoidmediated down regulation of membrane bound L-selectin and CD18 on PMN increased mammary gland susceptibility to Staphylococcus aureus following experimental challenge.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of dexamethasone on bovine neutrophil function are generally thought to be immunosuppressive: reducing phagocytosis (36), antibody-dependent cell-mediated cytotoxicity (36,38), and generation of reactive-oxygen species (25,36,38). In particular, dexamethasone downregulates neutrophil cell surface expression of the adhesion molecule L-selectin (CD62L) (7,25) and the ␤ 2 -integrin CD18 (7), which should intuitively reduce neutrophil extravasation. Conversely, there is evidence that dexamethasone enhances chemotactic ability, as neutrophils taken from dexamethasone-treated cattle show increased migration to C5a and IL-8 (1).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased margination of neutrophils might be caused by the recognized ability of corticosteroids to reduce neutrophil adhesion to the vascular endothelium. This effect is well explained by the decreased expression of adhesion molecules of the L-selectin and β 2 -integrin (CD18) families on neutrophils [7,9,23] in combination with the inhibition of the expression of endothelial-leukocyte adhesion molecule 1 (ELAM-1) and intercellular adhesion molecule 1 (ICAM-1) [12]. Although these changes impair neutrophil migration kinetics, which increase susceptibility to infectious diseases, such as bovine mastitis, they require additional immunological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticosteroids have been shown to cause leukocytosis involving neutrophilia and lymphopenia [36], suppression of leukocyte blastogenesis [26,30,33] and to change T-lymphocyte subpopulation patterns [2,8,16]. The increase in the number of circulating neutrophils following the administration of glucocorticosteroids has been well explained by the down-regulation of L-selectin and adhesion molecules of the β2-integrin family on these cells, resulting in an impaired ability of neutrophils to leave the circulation [9,23]. In addition, an increased release of neutrophils from bone marrow has been observed following the administration of corticosteroids [32].…”
Section: Introductionmentioning
confidence: 99%